Analysis of the Readability of Discourse in Indonesian Language Textbooks Grade VII Through Fry's Graph Formula at SMP Negeri 1 Puncak Sorik Marapi Mandailing Natal Regency - Rangkuti, Febri Aulia; Pane, Akhiril; Nursyaidah, Nursyaidah (Jurnal Hata Poda, 2024)
A very important learning resource in supporting learning in the classroom is textbooks. SMP Negeri 1 Puncak Sorik Marapi makes textbooks the main learning resource. Textbooks must be understandable and comprehensible to students to support a teaching programme. The textbook that is the object of this research is the Indonesian language textbook for class VII of the independent curriculum at SMP Negeri 1 Puncak Sorik Marapi, Mandailing Natal Regency. The purpose of this research is to find out how the readability of discourse in Indonesian textbooks grade VII of the independent curriculum through the fry chart formula at SMP Negeri 1 Puncak Sorik Marapi. This type of research is descriptive qualitative research. The data collection techniques used are observation and text study. The data analysis techniques used in this research are descriptive qualitative techniques and the fry chart formula. The discourse that becomes the sample in this research is 15 discourses. The results of this study show that there are 9 discourses that do not match the readability with grade VII and 6 discourses are appropriate. From the results obtained, it is concluded that the Indonesian language textbook for grade VII of the independent curriculum is not suitable for grade VII. . Keywords: Readability, Wacana, Fry Graph